2014
DOI: 10.1071/an14243
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the growth and meat tenderness of Brahman and F1 Senepol × Brahman steers

Abstract: The growth of 116 Brahman (BRAH) and 96 F1 Senepol × Brahman (F1 SEN) steers grazing improved Buffel pasture in the Northern Territory was compared. Average growth was 10 kg higher in F1 SEN during grazing in the 9 months following weaning. Twenty-five steers of each genotype were compared for feedlot performance and meat quality. There was no significant difference in feedlot growth over 73 days in a commercial feedlot. On average F1 SEN carcasses graded two boning groups lower in the Meat Standards Australia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In stark contrast to these earlier publications is a study reporting that Senepol × Brahman steers produced a more tender meat than purebred Brahman steers (shear force values after 14 days of aging of 34 N and 39 N, respectively) [ 64 ]. In addition, other than hump height, most of the carcass measures were similar for the two genotypes, and it was suggested that this crossbreed demonstrated a viable method to improve the meat quality of cattle produced in Northern Australia.…”
Section: Carcass and Meat Qualitymentioning
confidence: 99%
“…In stark contrast to these earlier publications is a study reporting that Senepol × Brahman steers produced a more tender meat than purebred Brahman steers (shear force values after 14 days of aging of 34 N and 39 N, respectively) [ 64 ]. In addition, other than hump height, most of the carcass measures were similar for the two genotypes, and it was suggested that this crossbreed demonstrated a viable method to improve the meat quality of cattle produced in Northern Australia.…”
Section: Carcass and Meat Qualitymentioning
confidence: 99%
“…The results indicated that using biological type A sires has no positive impact on the WW210 in calves of this population. Similar results were reported in a crossbred population descendant of a taurine adapted breed (Senepol) and females of biological type N, which is considered a viable cross for improving meat quality traits; however, no significant difference was observed for growth traits (Schatz et al ., 2014). Higher weaning weight was reported in progenies of sires of biological type N or B in comparison to type A sires, when they were mated with type B cows or crossed cows, 1/2N1/2B and 3/4B1/4N (Baker et al ., 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the heterosis effect on individual performance, maternal heterosis results in maternal environmental benefit and higher milk yield, which allows for higher calf growth during the lactation (Leal et al ., 2018). Some studies have reported the influence of cows (Meyer et al ., 1994; Leal et al ., 2018; Mendonça et al ., 2019) and bulls (Baker et al ., 2001; Schatz et al ., 2014; Cardoso et al ., 2018) breed compositions on the calf performance, assessing mainly the weaning weight. However, environmental factors such as the nutritional and health management of the herd, body condition and age of the dam at calving may impact calf growth, being the latter factor of great relevance as it affects the maternal–offspring behaviour and milk production (Silva et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It has been described as the “all-purpose American breed “and was developed by hybridization of the Brahman and Simmental breeds (Gouws, 2016 ). Generally, crossbreeding of Brahman with Taurine breeds produces hardy animals with better meat quality than purebred Brahmans (Crouse et al, 1989 ; Johnson et al, 1990 ; Schatz et al, 2014 ). The high tolerance of Simbra to harsh conditions (e.g., heat, humidity, parasites, seasonally poor pasture quality, and large distances required to be walked while grazing) is thus derived from its Brahman parentage.…”
Section: Introductionmentioning
confidence: 99%